2012
DOI: 10.22146/ijc.21371
|View full text |Cite
|
Sign up to set email alerts
|

KINETICS AND EQUILIBRIUM MODEL OF Pb(II) AND Cd(II) ADSORPTION ONTO TETRAKIS-THIOMETHYL-C-4-METHOXYPHENYLCALIX[4]RESORCINARENE

Abstract: The ability of tetrakis-thiomethyl-C-4-methoxyphenylcalix[4]resorcinarene for trapping Pb(II) and Cd(II) from aqueous solution at different pH, contact times, and initial metal concentration was investigated. Concentration of metal ions before and after interaction was analyzed by Atomic Absorption Spectrophotometer (AAS). The result indicated that tetrakis-thiomethyl-C-4-methoxyphenylcalix[4]resorcinarene is a good host for metal ions, where Cd(II) sorption capacity was higher than that of Pb(II). Effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
2
7
0
2
Order By: Relevance
“…On the other hand, for adsorbent 2b and 2c, the adsorption kinetics of Cd(II) and Cr(III) followed kinetics model of Ho while for the Cu(II) followed Lagergren kinetic models. These results are similar by previous researchers [22] showed that adsorption of Cr(III) onto polypropylcalix [4]arenes followed the kinetics model of Ho. By using the three adsorbents, shows that the adsorption rate constant for Cr(III) is greatest when compared to the adsorption of Cd(II) and Cu(II).…”
Section: Adsorption Kinetic Modelssupporting
confidence: 92%
“…On the other hand, for adsorbent 2b and 2c, the adsorption kinetics of Cd(II) and Cr(III) followed kinetics model of Ho while for the Cu(II) followed Lagergren kinetic models. These results are similar by previous researchers [22] showed that adsorption of Cr(III) onto polypropylcalix [4]arenes followed the kinetics model of Ho. By using the three adsorbents, shows that the adsorption rate constant for Cr(III) is greatest when compared to the adsorption of Cd(II) and Cu(II).…”
Section: Adsorption Kinetic Modelssupporting
confidence: 92%
“…Even at the low concentration, Pb(II) pollution could damage the central nervous system and cause mortality [8]. Therefore, Pb(II) removal process has gained the highest interest over the past several years [9][10][11][12][13].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Research work on different calix [4]resorcinarenes and proposing new efficient and green methods for their preparation is worldwide conducted. [12][13][14][15][16][17][18][19][20][21] Design and preparation of different types of lattice host molecules and investigating their ability to form different forms of crystalline materials with different potential applications are, therefore, of our main interest. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Compounds 6-9 were reported in literature to be prepared in alcoholic acid catalyzed solutions as a mixture of two conformers; chair and boat were formed.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Compounds 6-9 were reported in literature to be prepared in alcoholic acid catalyzed solutions as a mixture of two conformers; chair and boat were formed. [13,[15][16][17][18][19][20] In this work, the selective solvent-free formation of one isomeric product and the bioactivity of C-(p-substituted phenyl)calix [4] Scheme 1: Synthetic route for C-(p-substitutedphenyl)calix [4]resorcinarene 6-9. [36]…”
Section: Introductionmentioning
confidence: 99%